Pseudoaneurysm associated with arteriovenous fistula involving a superficial breast arteriole after vacuum-assisted removal of a benign mass: A case report. Issue 36 (September 2018) - Li, Yixuan; Wu, Zhoupeng; Yan, Feng; Peng, Yulan; Ma, Lang; Zeng, Guojun; Lv, Qing
Abstract: Rationale: Pseudoaneurysm (PA) with associated arteriovenous fistula (AVF) is most often secondary to vascular catheterization, percutaneous biopsy, surgery, or trauma. PA-AVF occurs mainly in large or median arterial territories but rarely in the superficial arterioles of the breast. Patient concerns: A 30-year-old woman underwent vacuum-assisted removal of breast fibroadenomas under ultrasonic guidance. On the follow-up visit, the patient complained of a painful enlarging lump in her left breast. Diagnoses: An iatrogenic breast PA-AVF was diagnosed. Interventions: The patient was treated with surgical excision and ligation under local anesthesia. Outcomes: At the 1-month follow-up, the wound was found to have healed well, and breast PA-AVF was eradicated. Lessons: Vacuum-assisted removal has been the first-line intervention for benign mass resection because of minimal invasion, but the risk of serious vascular complications remains. Careful duplex ultrasound examination prior to the procedure is highly recommended.